2006
DOI: 10.1016/j.crme.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of energy pumping in acoustics

Abstract: This Note presents an experimental vibro-acoustic set-up that aims to reproduce the energy pumping phenomenon between an acoustic medium and an essentially nonlinear oscillator. It shows a one-way irreversible transfer of energy between the first acoustic mode in a tube and a thin visco-elastic membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 5 publications
0
41
0
Order By: Relevance
“…In the field of structural vibration, a wide variety of NES designs with different types of stiffness (cubic , non-polynomial, non-smooth nonlinearities...) has been proposed [4,5,6,7]. In the acoustic field, to the best of our knowledge only one type of vibro-acoustic NES design has been tested, see the series of papers [8,9,10,11,12]. It was demonstrated that a 20 passive control of sound at low frequency can be achieved using a vibroacoustic coupling between the acoustic field (the primary system) and a geometrically nonlinear thin clamped structure (the NES).…”
Section: Strongly Modulated Responses (Smr)[3]mentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of structural vibration, a wide variety of NES designs with different types of stiffness (cubic , non-polynomial, non-smooth nonlinearities...) has been proposed [4,5,6,7]. In the acoustic field, to the best of our knowledge only one type of vibro-acoustic NES design has been tested, see the series of papers [8,9,10,11,12]. It was demonstrated that a 20 passive control of sound at low frequency can be achieved using a vibroacoustic coupling between the acoustic field (the primary system) and a geometrically nonlinear thin clamped structure (the NES).…”
Section: Strongly Modulated Responses (Smr)[3]mentioning
confidence: 99%
“…It was demonstrated that a 20 passive control of sound at low frequency can be achieved using a vibroacoustic coupling between the acoustic field (the primary system) and a geometrically nonlinear thin clamped structure (the NES). In [8,9,12], the thin baffled structure consists of a simple thin circular latex (visco-elastic) membrane whereas in [10] a loudspeaker used as a suspended piston is considered. In both cases, the 25 thin baffled structure has to be part of the frontier of the closed acoustic domain (to be controlled).…”
Section: Strongly Modulated Responses (Smr)[3]mentioning
confidence: 99%
“…A series of papers [1,2,3,4] demonstrated that a passive control of sound at low frequencies can be achieved using a vibroacoustic coupling between the acoustic field (the primary system) and a geometrically nonlinear thin baffled structure (the nonlinear absorber). In [1,2], the thin baffled structure consists of a simple thin circular visco-elastic membrane whereas in [3,4] a loudspeaker used as a suspended piston is considered.…”
Section: Introductionmentioning
confidence: 99%
“…In [1,2], the thin baffled structure consists of a simple thin circular visco-elastic membrane whereas in [3,4] a loudspeaker used as a suspended piston is considered. In the four papers, theoretical and experimental results are reported considering transient and periodic external excitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation